314. A multi-centre study to evaluate physical acceptance reference values, tolerances and action levels for a new PET/CT scanner. (December 2018) - Sardina, D.; Politi, G.; Abbate, B.; Gallias, K.K.; Caputo, V.; Brogna, A.; Candiano, G.; Piraneo, S.; De Vincolis, R.; Rabito, A.; Pedalino, A.; Occhipinti, A.; et al.
Abstract : Purpose: A multi-centre study to evaluate performances of PET/CT scanners and to draft a unique QC protocol for five departments was performed. The variability in quantitation of PET acceptance tests was investigated to define acceptance limits of these data establishing reference values and new tolerances to compare with the technical specifications provided by the manufacturer. Methods: Spatial resolution, scatter fraction, sensitivity, count rate loss and random coincidence estimation, Noise Equivalent Count Rate (NECR) and Image quality parameters were calculated following NEMA NU2-2012[1] standard on the new PET/CT scanners Biograph mCT Siemens installed in five different nuclear medicine departments. For each parameter, we assessed the consistency of the related data. Results: The acceptance test results demonstrated comparable output for all parameters investigated. A summarize schematic results were proposed and their relative variations and tolerances were discussed. As expected, the spatial resolution showed the least variability amongst all features related to its operator-independent preparation and strictly depending on equipment construction. Conversely, the sensitivity was the most variable parameter correlated to very low activity concentration required by NEMA protocol. We reported, for one scanner, an unexpected value in the count rate accuracy test (relative mean error @ peak NEC), despite the consistency of the values of peak NEC rate obtained. Conclusions: Based on this investigation, new tolerances of performance measurements were calculated and suggested employing a common platform for quality assurance procedures to minimize variability of physical reference values. The results showed the need for a multi-centre inter-comparison especially in the tests without the tolerances of technical specifications suggested by the manufacturer.